Thermal Modalities Including Hot Baths and Cold Plunges Play a Unique Role in Injury Prevention and Recovery - Kiera L. Vrindten, M.B.S.; Danielle P. Lonati, B.A.; Jillian L. Mazzocca, B.A.; Elizabeth G. Matzkin, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
There are several different modalities for injury prevention to consider in order to help our patients’ reach their ultimate goals. The purpose of this review is to analyze the use of hot and cold therapies to prevent injury. Thermotherapy has been used in clinical rehabilitation settings to treat health conditions. The therapeutic use of cold, known as cryotherapy, is historically the most popular treatment for acute musculoskeletal injury or fatigue. Cold therapy was seen to decrease delayed-onset muscle soreness and help resolve global or generalized muscle injury or fatigue. In sum, both cold and hot therapy play similar but unique roles in injury prevention and recovery. The key to effective use of either depends on understanding the nature of the injury and mastering the appropriate timing of therapeutic application. By leveraging the unique mechanisms of each modality, athletes can optimize their recovery process and reduce the risk of future injury. Level of Evidence: Level V, expert opinion.